Aerobic exercise training resets the human skeletal muscle methylome 10 years after breast cancer treatment and survival. Issue 1 (21st December 2022) - Gorski, Piotr P.; Raastad, Truls; Ullrich, Max; Turner, Daniel C.; Hallén, Jostein; Savari, Sebastian Imre; Nilsen, Tormod S.; Sharples, Adam P.
Abstract: Cancer survivors suffer impairments in skeletal muscle in terms of reduced mass and function. Interestingly, human skeletal muscle possesses an epigenetic memory of earlier stimuli, such as exercise. Long‐term retention of epigenetic changes in skeletal muscle following cancer survival and/or exercise training has not yet been studied. We, therefore, investigated genome‐wide DNA methylation (methylome) in skeletal muscle following a 5‐month, 3/week aerobic‐training intervention in breast cancer survivors 10–14 years after diagnosis and treatment. These results were compared to breast cancer survivors who remained untrained and to age‐matched controls with no history of cancer, who undertook the same training intervention. Skeletal muscle biopsies were obtained from 23 females before(pre) and after(post) the 5‐month training period. InfiniumEPIC 850K DNA methylation arrays and RT‐PCR for gene expression were performed. The breast cancer survivors displayed a significant retention of increased DNA methylation (i.e., hypermethylation) at a larger number of differentially methylated positions (DMPs) compared with healthy age‐matched controls pre training. Training in cancer survivors led to an exaggerated number of DMPs with a hypermethylated signature occurring at non‐regulatory regions compared with training in healthy age‐matched controls. However, the opposite occurred in important gene regulatory regions, where training in cancer survivors elicited a considerable reduction in methylation (i.e., hypomethylation) in 99% of the DMPs located in CpG islands within promoter regions. Importantly, training was able to reverse the hypermethylation identified in cancer survivors back toward a hypomethylated signature that was observed pre training in healthy age‐matched controls at 300 (out of 881) of these island/promoter‐associated CpGs. Pathway enrichment analysis identified training in cancer survivors evoked a predominantly hypomethylated signature in pathways associated with cell cycle, DNA replication/repair, transcription, translation, mTOR signaling, and the proteosome. Differentially methylated region (DMR) analysis also identified genes: BAG1, BTG2, CHP1, KIFC1, MKL2, MTR, PEX11B, POLD2, S100A6, SNORD104, and SPG7 as hypermethylated in breast cancer survivors, with training reversing these CpG island/promoter‐associated DMRs toward a hypomethylated signature. Training also elicited a largely different epigenetic response in healthy individuals than that observed in cancer survivors, with very few overlapping changes. Only one gene, SIRT2, was identified as having altered methylation in cancer survivors at baseline and after training in both the cancer survivors and healthy controls. Overall, human skeletal muscle may retain a hypermethylated signature as long as 10–14 years after breast cancer treatment/survival. Five months of aerobic training reset the skeletal muscle methylome toward signatures identified in healthy age‐matched individuals in gene regulatory regions.